2014
DOI: 10.1007/s00397-014-0788-9
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced low-frequency relaxation in colloidal DGEBA/SiO2 suspensions

Abstract: Diglycidyl ether of bisphenol A (DGEBA) is widely exploited as an epoxy resin in adhesives and coatings. In this paper, it is used as an oligomer matrix for silicafilled nanocomposites. Rheological measurements show that the pure matrix obeys power-law relaxation dynamics in the vicinity of the dynamic glass transition of this lowmolecular-weight glass former. In the filled systems, a lowfrequency relaxation appears additionally to the structural α-process of the matrix. Considering the nanocomposites as Newto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
(43 reference statements)
2
11
0
Order By: Relevance
“…In our own work [Dannert et al (2014)], the calculated Peclet frequencies correspond rather well to the onset of the low-frequency process for higher concentrations. However, a critical look at our results for the samples with the lowest filler concentrations gives a hint for a deviation between calculated and measured onset frequencies.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our own work [Dannert et al (2014)], the calculated Peclet frequencies correspond rather well to the onset of the low-frequency process for higher concentrations. However, a critical look at our results for the samples with the lowest filler concentrations gives a hint for a deviation between calculated and measured onset frequencies.…”
Section: Introductionsupporting
confidence: 59%
“…In this context, we have recently investigated the influence of quasispherical silica nanoparticles (average radius of about 12.5 nm) on the linear viscoelastic behavior of the low-molecular weight glass-former Diglycidyl Ether of Bisphenol A (DGEBA) [Dannert et al (2014)]. Interestingly, in the sheared nanocomposites with filler weight concentration 0.05 x 0.4 (corresponding to a volume concentration range 0.026 x V 0.25), a low-frequency relaxation-essentially manifesting itself by a plateaulike behavior of the storage modulus-emerged additionally to the a-process of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Since the experimental results, which are mainly discussed in the following, are obtained from rheological measurements at very low frequencies, the reliability of data when the phase angle approaches 90°needs to be discussed. Figure 1 shows the master curves (δ(a T ω)) of the loss angle (δ = tan −1 (G ″ /G ′ )) obtained for DGEBA/SiO 2 (r BPA = 0) suspensions with volume concentrations, x V = 0 , 0.054 , 0.11 , 0.18 and 0.25 (from the measurements published in Dannert et al (2014)). …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Wideband dielectric spectroscopy (Capaccioli et al 1998;Corezzi et al 2002) also does not give a hint to slow relaxation processes in pure DGEBA. The situation changes when adding nanoscaled filler particles to the DGEBA matrix: In previous works, Dannert et al (2015Dannert et al ( , 2014 have published data on a low-frequency relaxation process observed in colloidal suspensions formed by DGEBA and spherical silica nanoparticles. In contrast to other matrix relaxation processes found in DGEBA such as α-relaxation, β-relaxation and the strong γ-relaxation, the newly reported low-frequency process does not show an independent temperature dependency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation